A wastewater treatment system combining Myriophyllum aquaticum and activated sludge: Optimization of construction conditions and evaluation of wastewater treatment performance. (1st April 2019) - Guo, Xuan; Li, Yanmei; Zhong, Hua; Li, Peng; Zhao, Tongke; Zhang, Chengjun
Abstract: Although Myriophyllum aquaticum exhibits efficient nitrogen and phosphorus removal from wastewater, it has poor performance on organic matter removal. Here, a wastewater treatment system combining M. aquaticum and activated sludge was developed to improve its removal of organic matter. The Box–Behnken response surface methodology was used to optimize the construction conditions of the system, and the effects of time, temperature, illumination intensity, pollutant load, and dissolved oxygen (DO) on plant mass increment ( PMI ) and microbial biomass ( MB ) of the system were investigated. The wastewater remediation potential of the system was then evaluated. The results show that temperature and illumination intensity significantly affected PMI ( p < 0.01), and that time, pollutant load, and DO were the most significant factors affecting MB ( p < 0.01). The optimal construction conditions were 18.77 days in length, a temperature of 20.42 °C, an illumination intensity of 5827.61 Lx, a pollutant load of 120.61 mg/g plant, and a DO of 3.21 mg/L. The inoculation of activated sludge caused MB of the system to increase by four times relative to the non-inoculated system, suggesting successful formation of biofilms on M. aquaticum . Additionally, the removal of chemical oxygen demand (COD) from wastewater was significantly enhanced by the combined approach compared with a system relying solely on M. aquaticum. This study provides a new method for improving the remediation efficiency of M. aquaticum by combining the use of this species and activated sludge. Highlights: A system was constructed by the combined use of M. aquaticum and activated sludge. Response surface methodology was used for optimizing system conditions. Biofilm attached onto was successfully M. aquaticum formed. Organic matter removal potential by the system was significantly enhanced.